The congenital popliteal vasculature patterns in fibular free flap reconstruction by means of surgical anatomy in cadavers - Mathee Ongsiriporn (Nature Portfolio, 2021)
Abstract Fibular free flap (FFF) is frequently used for reconstruction requiring vascularized bone. Thus, understanding its vasculature variation is crucial. This study investigates the popliteal artery branching variations in Thai cadavers and compares them with previous studies. One hundred and sixty-two legs from 81 formalin-embalmed cadavers were dissected. The popliteal artery branching patterns were classified. The previous data retrieved from cadaveric and angiographic studies were also collected and compared with the current study. The most common pattern is type I-A (90.7%). For the variants, type III-A was the majority among variants (6.2%). Type IV-A, hypoplastic peroneal artery, was found in one limb. A symmetrical branching pattern was found in 74 cadavers. Compared with cadaveric studies, type III-B and III-C are significantly common in angiographic studies (p = 0.015 and p = 0.009, respectively). Type I-A is most common according to previous studies. Apart from this, the prevalence of type III-A variant was higher than in previous studies. Furthermore, type III-B and III-C are more frequent in angiographic studies which might be from atherosclerosis. Thus, if the pre-operative CTA policy is not mandatory, the patients at risk for atherosclerosis and population with high variants prevalence should undergo pre-operative CTA with cost-effectiveness consideration.